Electro-optically modulated lossy-mode resonance - Śmietana, Mateusz; Janaszek, Bartosz; Lechowicz, Katarzyna; Sezemsky, Petr; Koba, Marcin; Burnat, Dariusz; Kieliszczyk, Marcin; Stranak, Vitezslav; Szczepański, Paweł (Nanophotonics (Berlin, Germany), 2022)
Sensitivity, selectivity, reliability, and measurement range of a sensor are vital parameters for its wide applications. Fast growing number of various detection systems seems to justify worldwide efforts to enhance one or some of the parameters. Therefore, as one of the possible solutions, multi-domain sensing schemes have been proposed. This means that the sensor is interrogated simultaneously in, e.g., optical and electrochemical domains. An opportunity to combine the domains within a single sensor is given by optically transparent and electrochemically active transparent conductive oxides (TCOs), such as indium tin oxide (ITO). This work aims to bring understanding of electro-optically modulated lossy-mode resonance (LMR) effect observed for ITO-coated optical fiber sensors. Experimental research supported by numerical modeling allowed for identification of the film properties responsible for performance in both domains, as well as interactions between them. It has been found that charge carrier density in the semiconducting ITO determines the efficiency of the electrochemical processes and the LMR properties. The carrier density boosts electrochemical activity but reduces capability of electro-optical modulation of the LMR. It has also been shown that the carrier density can be tuned by pressure during magnetron sputtering of ITO target. Thus, the pressure can be chosen as a parameter for optimization of electro-optical modulation of the LMR, as well as optical and electrochemical responses of the device, especially when it comes to label-free sensing and biosensing.
Keywords: transparent conductive oxides (TCOs); magnetron sputtering; label-free sensing; lossy-mode resonance; electro-optical modulation; optical fiber sensor